2005
DOI: 10.1021/ci050178a
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of the Relation between Myosin Phosphorylation and Stress Development in Smooth Muscles

Abstract: In this paper the 4-state latch bridge model proposed by Rembold and Murphy is expanded; first by incorporation of the analytical expression of Ca2+ dependent MLCK activation from the work of Kato et al. and second, by inclusion of the myosin dephosphorylation based on the Michaelis-Menten kinetics. The analysis of the proposed model and the comparison with the original model results as well as with the experimental data is presented. The model is able to predict the steady-state isometric stress and the myosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
(108 reference statements)
0
12
0
Order By: Relevance
“…Moreover, the half saturation time for achieving the final active MLCK form for [Ca 2+ ] i = 0.1 µM is 1.5 s and for [Ca 2+ ] i = 0.5 µM it is 0.5 s. These results of the eight-state model show that the processes of activation/deactivation of MLCK are not as fast as proposed by earlier models (Kato et al, 1984) and some in vitro experiments on isolated CaM and MLCK (Kasturi et al, 1993;Torok et al, 1994). Moreover, the half-saturation time of MLCK activation/deactivation is of the same order of magnitude as the typical periods of oscillatory Ca 2+ signals in smooth muscle cells (Mbikou et al, 2006;Perez et al, 2005), thus the processes of MLCK activation significantly contribute to decoding of oscillatory Ca 2+ signal into a rather steady developed force already at the cellular level (Fajmut et al, 2008;Fajmut et al, 2005b;Mbikou et al, 2011;Mbikou et al, 2006) and add a small delay in force development after [Ca 2+ ] i increase.…”
Section: Cammentioning
confidence: 75%
See 4 more Smart Citations
“…Moreover, the half saturation time for achieving the final active MLCK form for [Ca 2+ ] i = 0.1 µM is 1.5 s and for [Ca 2+ ] i = 0.5 µM it is 0.5 s. These results of the eight-state model show that the processes of activation/deactivation of MLCK are not as fast as proposed by earlier models (Kato et al, 1984) and some in vitro experiments on isolated CaM and MLCK (Kasturi et al, 1993;Torok et al, 1994). Moreover, the half-saturation time of MLCK activation/deactivation is of the same order of magnitude as the typical periods of oscillatory Ca 2+ signals in smooth muscle cells (Mbikou et al, 2006;Perez et al, 2005), thus the processes of MLCK activation significantly contribute to decoding of oscillatory Ca 2+ signal into a rather steady developed force already at the cellular level (Fajmut et al, 2008;Fajmut et al, 2005b;Mbikou et al, 2011;Mbikou et al, 2006) and add a small delay in force development after [Ca 2+ ] i increase.…”
Section: Cammentioning
confidence: 75%
“…In our models (Fajmut et al, 2008;Fajmut et al, 2005b;Mbikou et al, 2011;Mbikou et al, 2006) we showed that the transduction of the Ca 2+ signal from its appearance in the cytosol as a time-dependent variation of concentration to the development of force in smooth muscle cells is decoded mainly by the interactions between Ca 2+ , CaM and MLCK, and is further translated to force by the balance between the phosphorylation and dephosphorylation of MLC, whereby both processes are regulated by MLCK and MLCP, respectively. The abundance of actomyosin crossbridges either phosphorylated or in the latch state is reflected in the magnitude of developed force.…”
Section: + -Contraction Couplingmentioning
confidence: 83%
See 3 more Smart Citations